THE IDENTIFICATION OF FUNGI CAUSES TINEA PEDIS ON RICE FARMERS IN JATIMULYA VILLAGE, BOALEMO REGENCY, GORONTALO - Annisa Nurqomariyah; Agusrianto Yusuf; Yolan Dunggio (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
Tinea Pedis is a dermatomycosis of the feet that often occurs between the fingers and soles of the feet. Generally, tinea pedis occurs in people who are often in humid places such as rice farmers. This study aims to identify the fungus that causes Tinea Pedis in rice farmers in Jatimulya Village, Boalemo Regency, Gorontalo Province. This research method is qualitative research and the data is analyzed descriptively. The sampling technique used purposive sampling method with a total sample of 8 people. Samples of skin scrapings near the lesion were taken aseptically and then cultured on Sabouraud Dextrose Agar media at room temperature for 12 days. Observations were made macroscopically and microscopically. The results showed that from skin scraping samples from Tinea pedis patients, 62.5% of dermatophytes were identified, namely the genus Trichophyton. In addition, non-dermatophyte fungi were also found, namely the genus Aspergillus and Metarhizium. Keyword: Identification, Tinea Pedis, Farmer, Fungi